2008
DOI: 10.1099/vir.0.2008/003590-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombination, decreased host specificity and increased mobility may have driven the emergence of maize streak virus as an agricultural pathogen

Abstract: Maize streak virus (MSV; family Geminiviridae, genus Mastrevirus), the causal agent of maize streak disease, ranks amongst the most serious biological threats to food security in subSaharan Africa. Although five distinct MSV strains have been currently described, only one of these – MSV-A – causes severe disease in maize. Due primarily to their not being an obvious threat to agriculture, very little is known about the ‘grass-adapted’ MSV strains, MSV-B, -C, -D and -E. Since comparing the genetic diversities, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
165
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(176 citation statements)
references
References 59 publications
10
165
1
Order By: Relevance
“…For example, suitable alternative names for MSV-A and MSV-B that reflect the different host preferences of viruses belonging to these strains would be MSV-Maize and MSVDigitaria, respectively [58]. Although a descriptive strain name could potentially be useful, it should be borne in mind that unless it genuinely reflects the characteristics of all members of a strain, it also could be quite misleading.…”
Section: Strain Namementioning
confidence: 99%
See 1 more Smart Citation
“…For example, suitable alternative names for MSV-A and MSV-B that reflect the different host preferences of viruses belonging to these strains would be MSV-Maize and MSVDigitaria, respectively [58]. Although a descriptive strain name could potentially be useful, it should be borne in mind that unless it genuinely reflects the characteristics of all members of a strain, it also could be quite misleading.…”
Section: Strain Namementioning
confidence: 99%
“…For example, whereas the ''A'' strain of MSV is clearly the only group of MSV variants that cause severe disease in maize [37,58], the ''A'' strain of WDV preferentially infects barley, whereas the ''C'' strain preferentially infects wheat [50].…”
Section: Rational Mastrevirus Species and Strain Demarcation Criteriamentioning
confidence: 99%
“…Monocotinfecting mastreviruses have previously been found throughout Africa (including the South-west Indian Ocean islands: SWIO), Europe, Japan, Southeast Asia, the island of Vanuatu, and Australia. Mastreviruses previously found on SWIO islands such as La Réunion and Mauritius include various maize streak virus (MSV) strains, sugarcane streak Réunion virus (SSRV) and sugarcane streak virus (SSV) [13,19,25,26].…”
mentioning
confidence: 99%
“…A great emphasis has been emerged here stressed on the biological difference between the viral isolates would be classified into different strains. For example, whereas the ''A'' strain of MSV is clearly the only group of MSV variants that cause severe disease in maize [28,42], the ''A'' strain of WDV favourably infects barley, whereas the ''C'' strain preferentially infects wheat [39], our Egyptian isolate of CpCDV could be assigned as a specific strain preferentially infects squash which is essentially a non-host species of this virus. Through recombination analysis performed using RDP4, it has been observed that the Egyptian isolate although more closely related to the Syrian isolate but a considerable part of the genome found to be originated from a different isolate of BeYDV assigned in the genbank under accession no ENA|DQ458791 (Fig.…”
Section: Discussionmentioning
confidence: 99%